Republic of Montenegro : Financial System Stability Assessment. (IMF Staff Country Reports; Country Report ;, 2008)
Montenegro is undergoing rapid credit growth in the context of heavy foreign bank presence and euro use. However, the rate of credit expansion is testing the limits of banks' capacity to underwrite loans prudently and maintain adequate buffers. Rapid credit growth is now also posing supervisory challenges, despite relatively strong financial sector regulation and supervision. The recommended policy response is a mix of prudential strengthening required to address risks emanating from rapid credit growth, and measures to address specific vulnerabilities.